Planning for the social and economic impact of HIV/AIDS in Malaysia - Ismail, Rokiah (1997)
The HIV epidemic has been spreading throughout the globe for more than 15 years, and it has been with us in Malaysia for at least 12 years . The HIV virus has been slowly but surely spreading throughout our population, without taking heed to social status, educational level, or upbringing. It affects anyone. Never has this world experienced a disease epidemic that lasts for so long without being able to curb its spread and prevent the devastating effects it has on the individual, society and nation. For, to date, there is no cure for this infection and there are no vaccines as yet to prevent the spread.